PENGARUH MODEL PEMBELAJARAN TGT TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMPN 22 PADANG - Adris, Azizah (Jurnal Edukasi dan Penelitian Matematika, 2023)
Improving communication skills in the context of mathematics has become essential to achieve success in the learning process. However, the reality is that eighth-grade students at SMPN 22 Padang still face challenges in their mathematical communication skills, which are not yet satisfactory. One possible approach to tackle this situation is to adopt the TGT (Teams-Games-Tournaments) instructional model. This lesson aims to identify and analyze the mathematical communication skills of eighth-grade at SMPN 22 Padang who follow the TGT learning model and whether it is superior compared to students who undergo direct instruction. This study employs quasi-experimental design and a non equivalent posttest only control group design. Sampling was carried out through the utilization of a straightforward random sampling technique, leading to the designation of VIII F for the experimental group and VIII D for control group. Final assessment instrument consists of written descriptions that measure mathematical communication abilities. The data analysis from this study indicates that P-value = 0.002, which is less than 0.05. This suggests that students who participated in TGT (Teams-Games-Tournament) learning model have superior mathematical communication abilities compared to students who underwent direct instruction.Keywords– Mathematical communication skill, Teams Games Tournament, Direct Learning